The Influence of E-WoM and Destination Image on Tourist Visiting Decisions to Ekasoghi Beach Sumenep Regency - Nurita Andriani; Nuri Ma'rifatullaili (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this research is to find out and analyze the effect of Electronic Word of Mouth (E-WoM) and destination image on tourist visit decisions to Ekasoghi Beach, Sumenep Regency. The method used in this research is quantitative. The population used is people who visit Ekasoghi Beach tourism. The sampling technique used the accidental sampling method, with a sample of 70 respondents. Methods of data collection using a questionnaire. The analytical method used is multiple linear regression analysis. The results of Electronic Word of Mouth (E-WoM) research have no partial effect on the decision to visit Ekasoghi Beach, Sumenep Regency, destination image has a partial effect on the decision to visit Ekasoghi Beach, Sumenep Regency, Electronic Word of Mouth (E-WoM) and destination image simultaneously influence the decision to visit Ekasoghi Beach, Sumenep Regency. The findings in this study indicate where the destination image factor greatly influences tourists in making a decision to visit Ekasoghi Beach.